Pengaruh Tax Avoidance, Earnings Persistence dan Sustainability Report terhadap Nilai Perusahaan dengan Dewan Komisaris Independen Sebagai Variabel Pemoderasi - Hardiyanti, Dwi; Lukita, Carolyn; Apriani, Fista (J-MAS (Jurnal Manajemen dan Sains), 2024)
Business performance, investor expectations and growth prospects are reflected in the firm's value. High value makes a business more attractive to shareholders and investors and makes it easier for companies to obtain external funding. The aims of this research is to analyze the effect of tax avoidance, earnings persistence and sustainability report on firm value and analyze the effect of tax avoidance, earnings persistence and sustainability report on firm value with independent board of commissioners as a moderating variable. Research in mining sector companies listed on the IDX for the period 2020-2022 uses quantitative methodology. A total of 97 companies became the population of this study. Purposive sampling was used in this study to collect data into 77 samples. The data analysis stage uses three steps, namely prediction testing, classical assumption testing, and statistical analysis of variance with SPSS software. The findings show that tax avoidance has no effect on firm value. However, firm value is influenced by sustainability report elements and earnings persistence. In addition, the independent board of commissioners has an influence in terms of strengthening/weakening the relationship between earnings persistence and sustainability report on firm value. Meanwhile, in tax avoidance, the board of commissioners has no influence in strengthening / weakening the relationship to firm value. The conclusions of this study have consequences for regulators and prospective shareholder. Findings from this research can be useful for policy makers, especially those related to tax avoidance, earnings persistence and sustainability reports to increase firm value in Indonesia.